Teaching English Poetry in EFL Classroom through Classroom Presentation - S Syamsia; Hamid Ismail (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2021)
The objective of this research was to know about how to teach English poetry in the EFL classroom through classroom presentation. Poetry has been used in teaching and learning English in the classroom. Many educators have attempted to deal with poetry in the EFL classroom. English poetry is a subject in the fifth semester of the English Department at STKIP Kie Raha Ternate. The research design used in this research is qualitative research. The population in this research was all students of the English Department of STKIP Kie Raha Ternate, and the samples of this research were 20 fifth-semester students of the English department of STKIP Kie Raha Ternate. To collect the data the researcher used classroom observation and documentation. To analyze the data, the researcher was analyzed the data from the result of classroom observation or in other words the researcher analyzes the result of classroom presentation. The analysis showed that classroom presentation can enhance the students’ achievement in learning poetry.